Institutional Management of Mangrove Ecosystems on Small Islands to Support Sustainable Utilization - Fibrianis Puspita Anhar (Niqosiya: Journal of Economics and Business Research, 2024)
Introduction: Tanakeke Island is one of the small islands in Indonesia that features mangrove ecosystems. In the 1980s, the area of mangroves on Tanakeke Island was approximately 1,770 hectares. However, between the 1980s and the 2000s, the mangroves were reduced by 60 percent due to uncontrolled exploitation and environmental changes. This paper aims to analyze the institutional linkages related to the current management of the mangrove ecosystem on Tanakeke Island and its impact on the sustainability of mangrove utilization. Research Methods: The analysis utilizes the concept of the dynamics of institutional resource management development (Ostrom, 1990) to assess the state of institutional management of the mangrove ecosystem and its relationship to sustainable use. Results: At the time of this research, Tanakeke Island had established rules governing mangrove utilization and rehabilitation activities. The mapping results indicate that the mangrove ecosystem management institutions on Tanakeke Island are currently in an “institutional self-governing period,” as defined by Ostrom (1990) framework for the dynamic development of natural resource institutions. Conclusion: The findings suggest that these management institutions are progressing toward self-governance, as they have demonstrated the ability to manage mangrove resources independently. At the time of this research, the institutions responsible for managing the mangrove ecosystem on Tanakeke Island support the sustainable utilization of mangroves.